Pengaruh Konten Kreatif, Engagement Rate dan Trust In Influencer Terhadap Brand Engagement Produk Glad2glow di Kalangan Gen Z Kota Denpasar - Ida Bagus Raka Suardana; Made Prema Putri Liemena (GEMILANG: Jurnal Manajemen dan Akuntansi, 2026)
Influencer marketing is a critical channel for reaching Generation Z, particularly in the skincare category. This study examines the effects of creative content (X1), engagement rate (X2), and trust in influencer (X3) on brand engagement (Y) with Glad2Glow among Gen Z in Denpasar. A quantitative approach was employed with 114 purposively selected Gen Z social media users. The instrument demonstrated acceptable validity (r > 0.30) and reliability (α > 0.60). Data were analyzed using multiple linear regression with standard classical assumption tests at the 5% significance level. Results indicate that all three predictors have positive and significant effects on brand engagement: creative content (β=0.360; t=5.840; p<0.001), engagement rate (β=0.484; t=7.718; p<0.001), and trust in influencer (β=0.210; t=3.576; p=0.001). The model is robust (F=91.195; p<0.001) and explains 70.5% of the variance in brand engagement (Adjusted R²=0.705). These findings underscore that the interplay of creative content quality, audience interaction activation, and influencer authenticity/credibility is pivotal to strengthening Gen Z’s brand engagement with Glad2Glow. Managerially, brands should prioritize interactive content formats, reinforce participation-oriented calls-to-action, and collaborate with influencers whose authenticity aligns with brand values.